2014
DOI: 10.1007/s10616-014-9692-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assessment of cell viability, proliferation and migration using real time cell analyzer system (RTCA)

Abstract: Cell viability and cell migration capacities are critical parameters for cell culture-related studies. It is essential to monitor the dynamic changes of cell properties under various co-culture conditions to our better understanding of their behaviours and characteristics. The real time cell analyzer (RTCA, xCELLigence, Roche) is an impedance-based technology that can be used for label-free and real-time monitoring of cell properties, such as cell adherence, proliferation, migration and cytotoxicity. The pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 16 publications
1
65
0
Order By: Relevance
“…We used RTCA, which is an impedance-based technology that can be used for label-free and real-time monitoring of cell properties, such as cell adherence, proliferation, migration and cytotoxicity. RTCA is also a powerful and reliable tool that can be used in drug discovery for toxicity and pharmacology studies434445. We found that SAHA treatment induced a time- and dose-dependent decrease in CI values in both cell lines.…”
Section: Discussionmentioning
confidence: 74%
“…We used RTCA, which is an impedance-based technology that can be used for label-free and real-time monitoring of cell properties, such as cell adherence, proliferation, migration and cytotoxicity. RTCA is also a powerful and reliable tool that can be used in drug discovery for toxicity and pharmacology studies434445. We found that SAHA treatment induced a time- and dose-dependent decrease in CI values in both cell lines.…”
Section: Discussionmentioning
confidence: 74%
“…However, these end-point assays need to destroy cells, leading to cell death or the destruction of cell structure. The real time cell analyzer (RTCA, xCELLigence, Roche) is an impedance-based technology that can be used for label-free and real-time monitoring of cell properties, such as cell adherence, proliferation, migration, and cytotoxicity, which could have widespread use [31]. In the detection of apoptosis at the molecular level, the normally detected proteins are caspase-9, caspase-3, and PARP (substrates of caspase-3), located in the mitochondrial pathway [32].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a clear need for an established cell line in the schistosome molecular tool-kit and progress in this endeavor is being made, especially for Schistosoma japonicum (see review by Ye et al (2013)). Finally, the introduction here of the xCELLigence approach to analyze non-model, less conventional cell lines such as Bge of B. glabrata , is notable and predicts follow-up studies to examine host-parasite interaction in more detail such as in Transwell/co-culture experiments (Roshan Moniri et al, 2014). With the increasing availability of sequence information of the genome and transcriptome of both the snail host and the schistosome, it is opportune and timely to optimize Bge cells as companion ‘tools’ to provide more fundamental information on the schistosome/snail host-parasite relationship, vector biology and indeed novel interventions.…”
Section: Discussionmentioning
confidence: 99%